IMPLEMENTASI BAI’ FUDHULI PADA PERUSAHAAN BESI TUA UD JAYA ABADI BANYUPUTIH SITUBONDO DENGAN PENDEKATAN ETIKA BISNIS ISLAM - Jonwari (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2020)
Islam gives color to every dimension of human life, including the economic world. This Islamic system tries to dialecticize economic values ​​with the values ​​of faith or ethics in accordance with Islamic teachings. especially in buying and selling transactions, which are required to meet all the requirements and bowls, in order to avoid the practice of Fudhuli as happened in the scrap metal company in Sumber Anyar Village, Banyuputih District, Situbondo Regency. Based on the conclusion, it can be seen that the practice of Fudhuli that occurs in the scrap metal company in Sumber Anyar Village, Banyuputih District, Situbondo Regency is in accordance with the Fudhuli theory which is explained in the fiqh books because one of the conditions for goods being transacted is not fulfilled, namely: property rights or ownership rights to the goods being transacted, as well as the application of business ethics through Fudhuli practice in accordance with the principle of honesty where after the goods are sold the owner is confirmed, and in accordance with the principle of responsibility and mutual help where the employees are selling the goods owned by the factory aims to help the factory where he works because he sees his goods are just wastedn.